The Impact of COVID-19 Pandemic on Homestays and Optimism in Kepulauan Seribu on Tourism Future through Smart Tourism - Ervan Ismail; Sumardjo Sumardjo; Djuara P. Lubis; Rilus A. Kinseng (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Tourism stakeholders must seek out innovative tactics to survive and thrive in the face of adversity. Switching to digital media and developing new digital inventions is thought to be the best option (Heliany, 2019; Irwan & Novianti, 2021). Based on this, we consider it important to see the impact of the COVID-19 pandemic on Kepulauan Seribu tourism and its relation to digital communication as an effort to minimize the impact of the pandemic which aims to see the optimism of homestay owners. This article provides an overview of the COVID-19 pandemic impact on tourism business owners of homestays in Kepulauan Seribu until 2021Objectives: This article provides an overview of the COVID-19 pandemic impact on tourism business owners of homestays in Kepulauan Seribu until 2021. This study aims to measure the awareness level of health protocols and the decline in income for homestay owners. This study also aims to describe the future recovery opportunities through the readiness of digital communication towards smart-tourism in Kepulauan Seribu and the optimism of homestay owners in developing their homestays in the future.Methodology: This study uses a quantitative descriptive approach. The collection of questionnaire data uses cluster sampling starting on June 23, 2021 until October 7, 2021 with a total of 308 respondents based on collected questionnaires. The study was carried out on 9 islands during the COVID-19 pandemic and under the policy of Restrictions towards Community Activities (abbreviated to PPKM) by Indonesia’s government. The presentation of descriptive data analysis uses SPSS Version 24. To strengthen the analysis, in-depth interviews were carried out with key informants.Finding: The results of data analysis show a 60% decrease in homestay income and the number of tourists during the COVID-19 pandemic. The biggest use of digital marketing is for imaging activity, followed by digital transaction activity, marketing, and receiving criticism and suggestions as only less than 50% of homestay owners have attended training. Although affected by the COVID-19 pandemic, homestay owners are optimistic to continue to develop the capacity of their homestay in the future.Conclusion: The availability of infrastructure to support smart tourism is sufficient. The readiness of human resources in the form of skills in maximizing the use of digital communication for tourism still needs to be supported through continuous digital communication training programs and assistance by tourism-aware groups. Keywords: COVID-19 pandemic; digital communication; Kepulauan Seribu; smart-tourism